Health literacy and active ageing among the population 65+ in the South Bohemian Region in the Czech Republic - Hellerová; Brabcová; Bártlová (Magyar Gerontológia, 2025)
Czechia is still experiencing an ageing population trend. The medium variant of the 2023 Projection (CZSO, 2023) suggests that by the end of the 2050s, the proportion of elderly (i.e. people aged 65 and over) should reach three and a quarter million people.